PELAKSANAAN KOORDINASI PEMBANGUNAN PARTISIPATIF DI DESA KAYU ARO KECAMATAN KAMPAR UTARA KABUPATEN KAMPAR TAHUN 2013 - Anita Idris; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Village is a tool to achieve the goals of national development, village is the leading government agency that can reach the real target group to be prosperous. In order to support the implementation of Law No. 32 Year 2004 on Regional Government and Law No. 25 Year 2004 on National Development Planning System, the construction of which is carried out by using the paradigm of empowerment is needed to realize the good of society participation in the planning, implementation and control of development village. The purpose of this study was to determine the coordination of the implementation of participatory and to determine the factors inhibiting of coordination in implementation of participatory development in Kayu Aro Village, North Kampar, Kampar District in 2013.The concept of theory used is the theory of coordination with the indicators in this research such as: Communication, cooperation, division of labor and a meeting / conference. As for the factors that affect several unsuccessful of coordination based on the researchers found in the field.Result of research, can be concluded that the implementation of coordination in participatory development in Kayu Aro Village, North Kampar, Kampar District in the category of less effective. In other words, there are still many problems that arise in its implementation. The limiting factor in the implementation of coordination in participatory development is communication and a meeting / conference. Both of these factors have an influence on the implementation of participatory development in Kayu Aro Village.Keywords: Coordination, Participatory Development, Communication, Cooperation, Division of Labor, Meeting/Conference.